Variations in Mediterranean Outflow Water and its salt discharge versus Pliocene changes in North Atlantic thermohaline circulation prior and during the onset of major Northern Hemisphere Glaciation, 3.7 – 2.6 Ma - Khélifi, Nabil (Christian-Albrechts-Universität zu Kiel, 2010)
Pliocene changes in Mediterranean Outflow Water (MOW) and its potential influence on northern North Atlantic thermohaline circulation prior and during the onset of Northern Hemisphere Glaciation (NHG; 3.7 – 2.6 Ma) were investigated at westernmost Mediterranean Site ODP 978 (1930 m w.d.) and along the northeast Atlantic continental margin, at Sites DSDP 548 (1250 m w.d.) and ODP 982 (1135 m w.d.). Foraminiferal δ18O records (and geomagnetic events) formed the base for stable isotope stratigraphy which led to a major revision of age control at Site 982. The Nd isotopic composition (εNd) of bottom seawater served to trace back the origin of water masses. Sea surface temperatures (SST) were reconstructed from the alkenone unsaturation index (U￼k'37) and Mg/Ca estimates on planktic shells. Bottom water temperatures (BWT) were estimated from Mg/Ca measured on epibenthic foraminifera. Epibenthic δ13C records were used as tracer of bottom water ventilation. This investigation consists of four interrelated studies. Study 1 provides new insights from proxy intercomparison. Uk'37￼-based vs Mg/Ca-based SST estimates at Site 982 show that SST values derived from alkenones are ~1°C higher than those based on Mg/Ca in planktic foraminifera. However, both proxies report similar climate trends. Over the period of fairly global stable climate between 3.7 and 3.3 Ma both proxies record a large orbital-scale variability that may be linked to changes in the strength and position of the North Atlantic atmospheric pressure systems and the position of the North Atlantic Current (NAC). From ~3.3 to 3.0 Ma northeast Atlantic SST underwent a major drop, a result that may contradict the PRISM concept assuming a time slice of largely constant climate conditions. Study 2 documents a major and long-term Upper Pliocene intensification of the Mediterranean outflow, 3.5 – 3.3 Ma. εNd values higher than -11 to -9 show that MOW spread continuously over the northeast Atlantic throughout the Upper Pliocene and reached up to the Rockall Plateau from ...